Lo strato lessicale armeno nella romaní: riconsiderazioni, ipotesi e un nuovo prestito (xem 'bordo del setaccio') (Atti del Sodalizio Glottologico Milanese, 2025)
Armenian loanwords represent a historically significant part of Early Romani lexicon. The number of loanwords that can be tracedback to this exogenous layer consists of about 50 lexemes. The phonetic shape shown by the Armenian loanwords in Romani implies that they have been acquired before the 11th century in a dialectal area that had not undergone the so-called 2nd Armenian consonant shift. The paper discusses some general issues regarding the Armenian layer in Romani and proposes some new observations about the phonological integration of Arm. ǝ and the loanwords endanis 'famliy' and patragi 'Easter, feast'. Finally, an Armenian origin is proposed for the Romani word xem 'edge of the sieve'.
Keywords: Romani; Armenian; Language Contact; Loanwords